Talented but Not Chosen—A Cross-Sectional Study—Do Coaches Release Late-Maturing Under-14 Players When Making Decisions? - Fabiana Parreira Bonito; Júlia Teles; Tiago Matos; Filipe Jesus; Anna Volossovitch; Carlos Barrigas; Maria Isabel Fragoso (Journal of Functional Morphology and Kinesiology)
Background: This cross-sectional study aims to clarify the relationship between coaches’ decisions and players’ relative age, biological maturation, and experience when identifying Under-14 (U14) players for the District and National Teams. Methods: A total of 360 male soccer players participating in the U14 national inter-association tournament, Lopes da Silva, were assessed. Birth dates were recorded, and players were categorized by birth quarter. Anthropometric measurements, fitness level (handgrip strength), and success indicators (performance evaluated by the coach, minutes played, and selection for the National Team) were documented, Maturation status was determined using bone age. Results: The majority of the sample was born in the 1st and 2nd quartiles regardless of maturation status. Morphological and functional differences between players born in different quartiles were no longer significant after controlling the effect of bone age. Late-maturing athletes played significantly fewer minutes. Among the players selected for the National Team, 89.9% were early or on-time maturers, and 92.9% were born in the first or second quartile of the year. While previous studies have shown reduced variability between bone and decimal age in the third and fourth quartiles, our findings indicate greater variability across all birth quartiles. Conclusions: Maturation status and relative age effect are crucial factors influencing coaches’ selection decisions. These findings highlight the need for a more equitable approach to talent identification, which should include track maturation bias avoiding the pursuit of short-term success and promoting long-term development programs for young soccer players. Undoubtedly, maturation status and relative age effect (RAE) play a significant role in a coach’s decision-making process.